BINDA COMPUTER RENTAL SYSTEM WITH VISUAL FOXPRO 6.0 - Hany Yusylia; Irfan Irfan, Skom, MMSI (Jurnal Sistem Informasi, 2000)
Writing research with the title: BINDA COMPUTER RENTAL SYSTEM WITHVisual Foxpro 6.0 explores the problems faced by Binda Computer as a computerrental service providers, such as calculating the cost of rent, payment receipt, sale andrental rating, using a program created with Visual FoxPro language OrientedDatabase6.0.All problems are outlined in Chapter III, which covers the problems, designingsystems from analysis to design input, process and output. Up to solving problemswith the programming language Visual FoxPro 6.0. with the expectation that thesesystems can help Binda Computer in running their business.